Exploring bioremediation strategies for heavy metals and POPs pollution: the role of microbes, plants, and nanotechnology - Karnwal, Arun; Martolia, Savitri; Dohroo, Aradhana; Al-Tawaha, Abdel Rahman Mohammad Said; Malik, Tabarak (Frontiers in Environmental Science, 2024)
Heavy metal and Persistent Organic Pollutants (POPs) pollution stemming from industrialization, intensive agriculture, and other human activities pose significant environmental and health threats. These contaminants persist in the air, soil, and water, particularly in industrialized nations, adversely affecting human health and ecosystems. While physical and chemical methods exist for detoxifying contaminated soil, they often have drawbacks such as high cost and technical complexity. Bioremediation, utilizing plants and microbes, offers a promising solution. Certain microorganisms like Streptomyces, Aspergillus and plant species such as Hibiscus and Helianthus show high metal adsorption capacities, making them suitable for bioremediation. However, plants' slow growth and limited remediation efficiency have been challenges. Recent advancements involve leveraging plantassociated microbes to enhance heavy metal removal. Additionally, nanotechnology, particularly nano-bioremediation, shows promise in efficiently removing contaminants from polluted environments by combining nanoparticles with bioremediation techniques. This review underscores bioremediation methods for heavy metals using plants and microbes, focusing on the role of Plant Growth Promoting Rhizobacteria (PGPR) in promoting phytoremediation. It also explores the implementation of nanotechnologies for eliminating metals from polluted soil, emphasizing the significance of soil microbiomes, nanoparticles, and contaminant interactions in developing effective nano-remediation strategies for optimizing agriculture in contaminated fields.